THE ALTHUSSERIAN RECOVERY OF SPINOZA: ESPISTEMOLOGY AND TOTALITY - Ricci Cernadas, Gonzalo (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
The paper aims to restitute the movement made by Louis Althusser for the purpose of thinking a non-Hegelian Marxism. This bet, not only theoretic, but political, means a detour by Baruch Spinoza, in order to rescue his thought. For this, considering studies of different commentators, we have proceeded to give an account of how those eminently spinozist topics, epistemology and totality, are specially fruitful to perform this althusserian task.